The role of time preference in smoking cessation: a longitudinal analysis of data from the Household Income and Labour Dynamics of Australia survey, 2001–08 - Brown, H; Adams, J (My University, 2013)
Aims Time preference describes how consideration of future events may affect present-day behavioural decisions. The aim was to establish whether time preference predicts smoking cessation in a longitudinal analysis. Design Secondary analysis of data from the Household Income and Labour Dynamics of Australia survey. Setting Australian community. Participants Members of the Household Income and Labour Dynamics of Australia survey panel, aged 15–64 years, who responded to at least four waves of data collection between 2001 and 2008, and reported any level of tobacco consumption at any wave. Measurements Smoking cessation was measured using a self-report questionnaire. Time preference was measured using self-reported time-period for financial planning. A range of socio-demographic and smoking-related covariates were controlled for. Findings A total of 1817 individuals were included in the analysis, representing 7913 separate observations. After controlling for socio-demographic and smoking-related covariates, the hazard ratio of quitting in those with longer versus shorter-term time preference (95% confidence intervals) = 1.28 (1.02–1.59). Conclusions Adult smokers with a longer-term time preference, who are more likely to consider future events when making present-day decisions, are more likely to quit smoking.
Keywords: Gender; Income & Finance; Activities; Education and Training; Health -- Addictive behaviours; Learning, education and training; Health and wellbeing; Income, wealth and finances; Gender; Education and Training; Health; Income & Finance; Activities; Addictive behaviours; Income, wealth and finances; Health and wellbeing; Learning, education and training